Efectos que produce la resolución emitida por la superintendencia de compañías, valores y seguros en las empresas constructoras ubicadas en el DMQ. Sector El Batán en el año 2017, que están obligadas a contar con un informe anual de auditoría externa. - Celi Herrera, Evelyn Carolina (2018)
The work presented below is intended to know the effects produced by the resolution issued by the Superintendence of Companies, Securities and Insurance in construction companies that exceed $500.000, 00 dollars in actives, located in the DMQ, Batán sector in the year 2017, which are obliged to have an annual external audit report. The external audit in Ecuador is briefly detailed, and what parameters an external auditor should follow at the time of the annual audit report. The deadlines for the delivery of the report are announced, as well as the type of sanctions that a company may receive when not complying with the regulations. It specifies the accounting and auditing standards that must be applied to the construction companies that are obliged to carry out an external audit, such as NIIF, NIC and NIA. It is determined that improvements had to be made by companies knowing that they must present the annual external audit report, both in their infrastructure, software and staff